GAMBARAN KOMUNIKASI PEMASARAN DAN LOYALITAS PELANGGAN PADA KOMUNITAS MY XL FORUM - Triatmojo, Benito Dani (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this study is to see the description of marketing communication and customer loyalty.Design / methodology / approach - The design of this study is cross sectional. This research uses descriptive approach with survey explanatory method as much as 83 respondents. A questionnaire was used as a research instrument to collect data from respondents. Analytical technique used is descriptive technique by using frequency table.Findings - Based on the results of the research using descriptive analysis, the result of the experience brand is in the high enough category with a score of representative 75.23% and the customer loyalty is in high category with a score of representative 76.40%.Originality / value - This research provides is condusted on telecommunication industry with the object of research is a sim card from famous brand. The dimensions and indicators used to measure of variable are the theories marketing mix.